2009
DOI: 10.1039/b916620c
|View full text |Cite
|
Sign up to set email alerts
|

Valence shell electronic spectroscopy of isoprene studied by theoretical calculations and by electron scattering, photoelectron, and absolute photoabsorption measurements

Abstract: The first ab initio calculations (vertical energies and oscillator strengths) are reported for the neutral electronic transitions of isoprene (2-methyl-1,3-butadiene), CH(2)CHC(CH(3))CH(2). The VUV photoabsorption spectroscopy of the molecule is presented in the energy range 4.6 to 10.8 eV (270-125 nm) with the highest resolution yet reported above 6.05 eV, revealing new spectral features. Valence and Rydberg transitions have been assigned in accordance with the theoretical results and the associated vibronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
8
16
0
Order By: Relevance
“…Evident from Fig. 1 is the good agreement between this discrete value (the red star) and the literature spectrum from Martins et al (2009), who reported σ isoprene = 1.29 × 10 −17 cm 2 molecule −1 . Taking into account potential systematic errors from e.g.…”
Section: Absorption Cross Sections (σ ) For Isoprenesupporting
confidence: 80%
See 2 more Smart Citations
“…Evident from Fig. 1 is the good agreement between this discrete value (the red star) and the literature spectrum from Martins et al (2009), who reported σ isoprene = 1.29 × 10 −17 cm 2 molecule −1 . Taking into account potential systematic errors from e.g.…”
Section: Absorption Cross Sections (σ ) For Isoprenesupporting
confidence: 80%
“…6), consistent with results from this work. A similar re-evaluation using cross sections from Martins et al (2009) does not change the rate coefficients from our study.…”
Section: Comparison Of K 1 With Literature Valuessupporting
confidence: 49%
See 1 more Smart Citation
“…In this study, we primarily evaluated the potential of monoterpenes including limonene, α‐pinene, and p ‐cymene and their structural unit, isoprene, as dopants for APPI. According to data available on photoabsorption cross sections, these species absorb the VUV photons from the krypton lamp as effectively as toluene and do not have positive electron affinities . Moreover, these compounds are natural compounds ubiquitous in nature and are considered less hazardous .…”
Section: Resultsmentioning
confidence: 99%
“…We summarize in Table I excitation energies computed with τ XCDFT along side with available benchmark data [36][37][38][39][40][41]. We find that the performance of τ XCDFT is comparable with XCDFT [7].…”
Section: B Quality Of the Excitation Energiesmentioning
confidence: 92%